The stages of the practice of Islamic requirements in muslim-majority institutions: a historical-comparative study of nurse uniform transformation in four Malaysian healthcare institutions - Salilah Saidun, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Societal changes take place from time to time and the dynamics of group change are explained by a few theories but they may not be able to expound the phenomenon in specific groups with different backgrounds. The nurse uniform transformation is one of the observable changes in Malaysian healthcare institutions since Malaysia gained its political independence in 1957 but no comparative study has examined the experience of different healthcare institutions. The paper examines these two knowledge gaps to assess the factors behind nurse uniform transformation in Malaysia and the dynamics of Muslim-majority group change concerning the practice of Islamic requirements using the historical-comparative cross-institutional case study method involving four healthcare institutions in Malaysia. The Malaysian nurse uniform manifests the early three-decade post-independence period of colonial heritage maintenance and the subsequent gradual revival of the Malay-Muslim identity. The religious-related factors were the dominant motivation fuelling the transformation of nurse uniforms in Malaysia. Based on the four cases, a refined theory on the stages of the practice of Islamic requirements in a Muslim society or Muslim-majority institution emerges from the findings. It explicates four cyclic phases that society experiences in revising the status quo. It starts with the maintenance of the status quo, followed by the stage of acquainting a new concept, which ensues to the phase of learning to accept the new concept, followed by the initiation of the new practice before the practice is accepted as a new status quo. The theory also illustrates society’s responses and the recommended approaches that advocates may adopt during each phase.